Surgical and functional outcomes of two types of transcutaneous bone conduction implants. Issue 12 (18th December 2020) - Scotta, G; Allam, A; Dimitriadis, P A; Wright, K; Yardley, M; Ray, J
Abstract: Objective: This study aimed to evaluate surgical and functional outcomes, in a tertiary referral centre, of two different types of semi-implantable transcutaneous bone conduction devices. Method: This study involved prospective data collection and review of patients implanted between November 2014 and December 2016. Glasgow Hearing Aid Inventory (Glasgow Hearing Aid Benefit Profile or Glasgow Hearing Aid Difference Profile) and Client Oriented Scale of Improvement were completed where appropriate. Surgical and audiological outcomes were recorded in the surgical notes. Results: Glasgow Hearing Aid Difference Profile and Glasgow Hearing Aid Benefit Profile showed similar mean score in the active and the passive transcutaneous bone conduction devices. Client Oriented Scale of Improvement showed improvements in listening situations. Post-operative speech reception threshold showed better mean threshold in the active transcutaneous bone conduction devices group when compared with the passive transcutaneous bone conduction devices group. No device failures or surgical complications existed in either group, with the surgical time being less in the passive transcutaneous bone conduction devices group. Conclusion: Both devices are reliable semi-implantable transcutaneous bone conduction devices with excellent surgical and functional outcomes and patient satisfaction. Overall surgical time was much less in the passive transcutaneous bone conduction devices group with no necessity for pre-planning. This is much easier to remove with the possibility of conversion to other devices in the manufacturer's portfolio and wide-ranging wireless accessories. Further studies are needed to assess the longer-term results in a bigger population.